Autophagy‐related genes polymorphism in hepatitis B virus‐associated hepatocellular carcinoma: A systematic review - Parastoo Yousefi; Alireza Tabibzadeh; Abdulhussain Kadhim Jawaziri; Mohsen Mehrjoo; Mandana Akhavan; Leila Allahqoli; Hamid Salehiniya (Immunity, Inflammation and Disease, 2024)
Abstract Background Chronic hepatitis B (CHB) virus is the most common risk factor for developing liver malignancy. Autophagy is an essential element in human cell maintenance. Several studies have demonstrated that autophagy plays a vital role in liver cancer at different stages. In this systematic review, we intend to investigate the role of polymorphism and mutations of autophagy‐related genes (ATGs) in the pathogenesis and carcinogenesis of the hepatitis B virus (HBV). Materials and Methods The search was conducted in online databases (Web of Science, PubMed, and Scopus) using Viruses, Infections, Polymorphism, Autophagy, and ATG. The study was conducted based on the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses criteria. Results The primary search results led to 422 studies. By screening and eligibility evaluation, only four studies were relevant. The most important polymorphisms in hepatocellular carcinoma were rs2241880 in ATG16L1, rs77859116, rs510432, and rs548234 in ATG5. Furthermore, some polymorphisms are associated with an increased risk of HBV infection including, rs2241880 in ATG16L1 and rs6568431 in ATG5. Conclusion The current study highlights the importance of rs2241880 in ATG16L1 and rs77859116, rs510432, and rs548234 in ATG5 for HBV‐induced HCC. Additionally, some mutations in ATG16L1 and ATG5 were important in risk of HBV infection. The study highlights the gap of knowledge in the field of ATG polymorphisms in HBV infection and HBV‐induced HCC.